Lithraea molleoides botanical characterization and antimicrobial study of hydrolat and oil essential obtained from leaves - Haedo, L. (2024)
Antimicrobial or pesticides resistance of microorganisms causing diseases or deterioration of plants causes to failure of clinical therapy or pest control respectively. This leads to an increase in antibiotic or pesticide doses to achieve the desired effect. For this reason, the antimicrobial or pesticide resistance of microorganisms are global public health problem. In recent years, alternatives to the use of antibiotics have been proposed, including the use of probiotics, prebiotics, symbiotics, and plant-based products. Lithraea molleoides_ (Vell.) Engl. belonging to the Anacardiaceae family, known in Argentina as “molle”, “molle de beber”, “molle blanco”. L. molleoides is a tree (2.5 to 9 m high) which grows in South America, especially in Argentina, Brazil and Uruguay. Botanic studies are important in order to establish the appropriate parameters to perform an effective quality control of plants. For this reason, the objective of the present work was to characterize ethnobotany and obtain essential oil (EO) and hydrolat from L. molleoides leaves to determine its antimicrobial activity. The plant material was collected during the spring of 2023 and the leaves were separated manually. The botanical description of L. molleoides was performed by determination of the micrographic parameters. The studies were illustrated by photomicrographs using a Leitz DMRB microscope with digital camera. L. molleoides were characterized by pharmacobotanical point of view, through various qualitative and quantitative characters micrographic. The aerial parts were herbalized and preserved in acetoalcoholic formalin or dried at 45°C. Samples were diafanized according to Dizeo. The qualitative micrographic characters were stomata type, leaf structure, presence of trichomes, presence of oleiferous glands, etc. Regarding the assessment of quantitative micrograph parameters, the following were taken into account: stomata number, stomatal index , palisade ratio , nerve terminals number and islets number. The EO and hydrolat were obtained by steam distillation using the leaves. Antimicrobial activity of hydrolat and EO against fungal phytopathogenic: Botrytis cirenea, Fusarium gramineae and Colletotrichum acutatum; and bacteria as Escherichia coli and Pseudomonas aeruginosa. The antimicrobial activity was evaluated by diffusion well method. The fungi were plated onto potato dextrose agar (PDA) while bacteria onto Luria-Bertani agar (LBA) by spreading a volume (100 μL) inoculum. Then, 6 mm diameter holes were punched aseptically, filled with 50 μL hydrolats or EO. Hydrolat showed antifungal activity only against C. acutatum while EO showed antibacterial activity. These results indicate that hydrolat could be used in formulations aimed at controlling some pests and EO as an antibacterial in pharmaceutical formulations. More studies will have to be carried out to identify the metabolites that have antimicrobial activity and their stability under different environmental conditions.